Discovery of a novel 3, 4-dimethylcinnoline carboxamide M4 positive allosteric modulator (PAM) chemotype via scaffold hopping. Issue 21 (1st November 2019) - Temple, Kayla J.; Engers, Julie L.; Long, Madeline F.; Gregro, Alison R.; Watson, Katherine J.; Chang, Sichen; Jenkins, Matthew T.; Luscombe, Vincent B.; Rodriguez, Alice L.; Niswender, Colleen M.; Bridges, Thomas M.; Conn, P. Jeffrey; et al.
Graphical abstract: Highlights: Novel 2.4-dimehtylcinnoline-based M4 PAMs. Utility of scaffold hopping to improve properties/DMPK. Balanced human and rat M4 PAM potency. Abstract: This Letter details our efforts to replace the 2, 4-dimethylquinoline carboxamide core of our previous M4 PAM series, which suffered from high predicted hepatic clearance and protein binding. A scaffold hopping exercise identified a novel 3, 4-dimethylcinnoline carboxamide core that provided good M4 PAM activity and improved clearance and protein binding profiles.